e-ViP: Ana-Lena Olofsson (Out of Print) - Chara Balasubramaniam (Association of American Medical Colleges, 2010)
Abstract This case describes the story of a virtual patient called Ana-Lena Olofsson, a 15-month-old girl with a history of loose stools and failure to thrive. As the case progresses, learners are able to determine a provisional diagnosis based on the history and examination findings. Learners have to decide on some initial investigations and interpret the results appropriately. By proceeding to specialist investigations, learners are able to confirm the diagnosis and then formulate a management plan. This virtual patient case has been repurposed as part of the Electronic Virtual Patient (e-ViP) program. e-ViP aims to create a bank of repurposed and enriched virtual patients available under a Creative Commons license. All e-ViP virtual patients have been repurposed using MedBiquitous Virtual Patient Technical Standards.